Optical remote sensing of land surfaces : techniques and methods - Baghdadi, Nicolas; Zribi, Mehrez (Remote sensing observations of continental surfaces set., 2016)
The considerable progress in instrumentation and in the development of methods for the processing and analysis of data places remote sensing at the center of various international programs for the surveillance and tracking of climatic and anthropogenic changes and effects on the environment. This volume presents optical imaging and LiDAR systems: their instrumentation, physics of measurement, processing methods and data analysis. The estimation of a digital terrain model based on optical images and LiDAR data is also discussed. This book, part of a set of six volumes, has been produced by scientists who are internationally renowned in their fields. It is addressed to students (engineers, Masters, PhD), engineers and scientists, specialists in Earth observation techniques and imaging systems. Through this pedagogical work, the authors contribute to breaking down the barriers that hinder the use of Earth observation data.